PENGARUH MODEL STAD TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN SOSIOLOGI DI SMA NEGERI 1 TEBAS - Anggriyani, Anggriyani; Zakso, Amrazi; Rustiyarso, Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ Â Â Â Â Â Â Â Â Â The problem in this research is â€œThe influence of the use of cooperative learning model of stad type on the of student achievement of class XI IPS on the learning of sociology in SMA Negeri 1 Tebasâ€. This study intended to know the influence of the use of cooperative learning model stad type on of student achievement of class XI IPS on learning sociology in SMA Negeri 1 Tebas. Quasi experiment was used in this research study with non-equevalent control groub design. The sampel of the research is student of class XI IPS2 (experimental class) and class XI IPS1 (control class) SMA Negeri 1 Tebas. The research showed that the average result of post-test control class 66,03 and average post-test experimental class 72,36. Furthermore t-test results obtaint t count of 2,06 t-table (a 5% with dk 52) of 1,6762. This study showed that the positive effect of STAD on student learning achievement.Â Keyword : influence, stad, learning sociology.